Challenges Faced by Students with Physical Impairments in Gilgit-Baltistan: A Parental Perspective - Sania Zahra; Khanam Zahra; Muhammad Hadi Haidari (Indus Journal of Social Sciences, 2025)
This study explores the challenges faced by students with physical impairments in Gilgit-Baltistan, Pakistan, from the parental perspective. Despite national and international policies advocating for inclusive education, the implementation in remote regions remains insufficient. Through a quantitative research design involving 65 parents, the study identifies academic, social, infrastructural, and attitudinal barriers that hinder the educational participation of children with physical impairments. Key findings highlight the lack of trained teachers, inadequate school infrastructure, and limited access to assistive technologies as major academic challenges. Socially, children face exclusion, bullying, and low self-esteem, exacerbated by negative societal attitudes and misconceptions about disability. Additionally, physical barriers such as inaccessible classrooms, lack of ramps, and poor transportation further limit educational access. The study emphasizes the need for improved teacher training, infrastructure upgrades, and stronger policy enforcement to ensure inclusive and equitable education for children with physical impairments in Gilgit-Baltistan. The findings underscore the importance of a multifaceted approach to overcoming barriers and promoting inclusion in the region’s educational system.